Metaphors as Tattoos on human body: Passion or Pathosis? (Bangladesh Journal of Medical Science, 2022)
Background:The trend of tattoos increases day-by-day in many of the countries but unfortunately there is no evaluation of this practice in Pakistan.The term “tattoo” is the art of making colourful designs beneath the skin. There are different types of tattoos with different colour of inks. This practice is done for many reasons including fashion, beauty, to hide skin marks, addiction to pain, to memorize something or due to any personal reasons. Some people hide their tattoos due to some restrictions. Tattooed people may face restriction in jobs. They may cause different type of skin infections and other medical conditions.Objective:Our motive of research is to evaluate the relation of tattoos with disease conditions and reasons for adaptation of tattoos in Pakistan.Methodology:The data was collected by online interviews and face-to-face interactions with participants and tattoo artists. All the participants (N=181) with permanent tattoos were asked about different questions regarding age, gender, motivations for being tattooed, opinions and side effects following tattooing etc.Results: In Pakistan, tattooing is more common among males (74.03%) than females (25.96%). The highest motivation of being tattooed was found to be fashion (31.57%) and beauty (36.31%). Greater number of participants considered tattooing as harmless (66%) and less considered it as harmful (28%), while few (N=6%) have mixed opinions. Common side effect experienced by participants was inflammation (23.36%) and then allergy (11.41%) but majority of the participants did not experience any severe side effects. People belonging to any occupation were equally influenced by tattooing but it is more common in teenagers.Conclusion:In Pakistan, tattoos trend seems to be increasing day-by-day. Most people regardless of age, occupation, religion and side effects got tattoos because of fashion and beauty and there were no severe side effects of tattooing in Pakistan.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 730-740